(untitled) (Northern International Medical College Journal, 2015)
Background : There is suboptimal growth observed among the very low birth weight (VLBW) infants during postnatal period. Objectives : This study was conducted to evaluate the anthropometric parameters among preterm VLBW infants during early period of life. Methods : This was a retrospective study of preterm VLBW infants admitted to Dhaka Shishu (Children) Hospital during the period of July 2011 to June 2013. Body weight, length and occipitofrontal circumference (OFC) at birth and at 4 weeks was recorded from neonatal data base. Z-scores for each anthropometric parameter were computed using Fentons growth chart of preterm infants. Statistical analysis was done using SPSS version 21.0. Results : Total 88 preterm VLBW infants were included in the study and among them male were 61.4% and female were 38.6% with a male female ratio 1.59:1. Mean weight, length and OFC at birth was 1186±277.45gm, 38.23±2.89 cm and 27.46±2.20cm respectively and at 4 weeks 1460.81±295.73 gm, 41.23±2.87 cm and 29.91±2.19 cm respectively. At birth small for gestational age (SGA) was found in 44.3% but at 4 weeks majority (77.3%) failed to achieve appropriate weight. Z score of weight, length and OFC at birth was -1.19, -0.58 and - 0.24 respectively and at 4 weeks-2.01, -1.17 and -0.75 respectively. There was a significant decline in all three anthropometric parameters from birth to 4 weeks of life (p<0.05). Conclusion : There was decrease in all anthropometric parameters among preterm VLBW neonate at 4 weeks of life. Despite significant decrease in somatic growth they maintained a near normal head growth. Northern International Medical College Journal Vol.7(1) Jul 2015: 115-118